Attitude of the Modulation Instability gain in Oppositely Directed Coupler with the effects of the Intrapulse Raman Scattering and Saturable Function - Houwe, Alphonse; Abbagari, Souleymanou; Saliou, Youssoufa; İnç, Mustafa; Doka, Serge Y.; Bouetou, Thomas B.; Bayram, Mustafa (Elsevier, 2021)
To establish the effects of the Higher-Order Dispersion (HOD) and Raman Scattering (RS) on Modulation Instability (MI) in the presence of the Saturable Function (SF), it is used the Coupled Nonlinear Schrodinger Equation (CNLSE) which describes pulses propagating in a higher optical beam in oppositely guided coupler. It has been shown through the MI gain spectra the power of the SF in the presence of HOD and Raman effects (RE). By utilizing the HOD with the saturable nonlinearity (SN), it is formed three sides lobes and some new MI bands emerged. On the same way, it is observed that the RE have more potency in the presence of saturable parameter (SP) in the normal and anomalous dispersion regime. It is important to mention that by varying the SF, third-order dispersion (TOD) and Group Velocity Dispersion (GVD) in the absence of Raman parameter (RP) it is obtained three sides lobes which is an supplementary results compare to Alves et al. (2020), Guerin et al. (1995) and Mohamadou et al. (2010). These results could be important to stress the dynamics of the MI in optical fibers such as optical amplification of poor signal, supercontinuum generation, data transmission and signal processing system and very fast transmission signal and so on.
Keywords: Modulation Instability; Oppositely directed coupler; Saturable Function